'CPR for Feet' care bundle to improve foot assessment in inpatient diabetes. Issue 3 (4th September 2018) - O'Regan, Rhea; MacDonald, Ross; Boyle, James G; Hughes, Katherine A; McKenzie, Joyce
Abstract : Aims: The Scottish Inpatient Diabetes Foot Audit conducted in 2013 revealed that 57% of inpatients had not had their feet checked on admission, 60% of those at risk did not have pressure relief in place and 2.4% developed a new foot lesion. In response, the Scottish Diabetes Foot Action Group launched the 'CPR for Feet' campaign. The aim of this project was to raise awareness of the 'Check, Protect and Refer' (CPR) campaign as well as improve the assessment and management of inpatients with diabetes. Methods: A quality improvement project underpinned by Plan-Do-Study-Act (PDSA) methodology was undertaken. The first and second cycles focused on staff education and the implementation of a 'CPR for Feet' assessment checklist using campaign guidelines, training manuals and modules. The third and fourth cycles focused on staff feedback and the implementation of a 'CPR for Feet' care bundle. Results: Baseline measurements revealed 28% of patients had evidence of foot assessment. Medical and nursing staff reported to be largely unaware of the 'CPR for Feet' campaign (13%). Fifty-two per cent of inpatients with diabetes had their feet assessed and managed correctly following the second PDSA cycle. After completion of the third and fourth PDSA this number improved further to 72% and all staff reported to be aware of the campaign. Conclusions: The introduction of a 'CPR for Feet' care bundle improved the assessment of inpatients with diabetes.